Clinical Characteristics and Risk Factor Analysis for Lower-Extremity Amputations in Diabetic Patients With Foot Ulcer Complicated by Necrotizing Fasciitis. Issue 44 (November 2015) - Chen, I-Wen; Yang, Hui-Mei; Chiu, Cheng-Hsun; Yeh, Jiun-Ting; Huang, Chung-Huei; Huang, Yu-Yao
Abstract : Abstract: Patients with diabetes are at a higher risk of having diabetic foot ulcers (DFUs) or necrotizing fasciitis (NF). The present study aims to examine the clinical characteristics and associated risk factors for lower-extremity amputation (LEA) in patients with DFU complicated by NF. We retrospectively reviewed patients treated at a major diabetic foot center in Taiwan between 2009 and 2014. Of the 2265 cases 110 had lower-extremity NF. Limb preservation outcomes were classified as major LEA, minor LEA, or limb-preserved. Clinical characteristics, laboratory data, and bacterial culture results were collected for analysis. Of the 110 patients with NF, 100 had concomitant DFUs (NF with DFU) and the remaining 10 had no DFU (NF without DFU). None of the NF patients without DFU died nor had their leg amputated. Two NF patients with DFU died of complications. The amputation rate in the surviving 98 NF patients with DFU was 72.4% (46.9% minor LEA and 25.5% major LEA). Seventy percent of the NF patients without DFU had monomicrobial infections (60% with Streptococcus species), and 81.4% NF patients with DFU had polymicrobial infections. Anaerobic organisms were identified in 66% of the NF patients with DFU. Multinomial logistic regression analysis revealed an association between high-grade Wagner wound classification (Wagner 4 and Wagner 5) and LEA (adjusted odds ratio [aOR] = 21.856, 95% confidence interval [95% CI] = 1.625–203.947, P  = 0.02 and aOR = 20.094, 95% CI = 1.968–205.216, P  = 0.01 for major and minor LEA, respectively) for NF patients with DFU. In addition, a lower serum albumin level was associated with major LEA (OR = 0.066, P  = 0.002). In summary, once DFUs were complicated by NF, the risk of amputation increased. Empirical treatment for NF patients with DFU should cover polymicrobial infections, including anaerobic organisms. The high-grade wound classification and low serum albumin level were associated with LEA.